2022
DOI: 10.3390/su14073742
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Emissions Induced by Vehicles Cruising for Empty Parking Spaces in an Open Parking Lot

Abstract: Parking lots are places of high air pollution as numerous vehicles cruise to find vacant parking places. Open parking lots receive high vehicle traffic, and when limited empty spaces are available it leads to problems, such as congestion, pollution, and driver frustration. Due to lack of return on investment, open parking lots are little studied, and there is a research gap in understanding the magnitude of CO2 emissions and cruising observed at open parking lots. Thus, this paper aims to estimate CO2 emission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Vehicles searching for an empty parking space may significantly lead to cruising and frequent stops, which increases CO 2 emissions [57]. Paidi et al [43] carried out a recent study to estimate the excess CO 2 emissions from drivers searching for vacant parking spaces during peak and non-peak hours. The study revealed that cruising distance and time are predominantly influenced by the number of empty parking spaces available and the driver's location within the parking lot.…”
Section: Impacts Of On-street Parkingmentioning
confidence: 99%
“…Vehicles searching for an empty parking space may significantly lead to cruising and frequent stops, which increases CO 2 emissions [57]. Paidi et al [43] carried out a recent study to estimate the excess CO 2 emissions from drivers searching for vacant parking spaces during peak and non-peak hours. The study revealed that cruising distance and time are predominantly influenced by the number of empty parking spaces available and the driver's location within the parking lot.…”
Section: Impacts Of On-street Parkingmentioning
confidence: 99%
“…Accurate zone‐wise parking slot predictions can be achieved for long term and short term in Feng et al 30 by using the deep learning framework dual Convolutional Long Short‐Term Memory with DenseNet (dConvLSTM‐DCN). Estimating CO 2 emission induced by the vehicle when the driver searches for an open parking slot discussed in work, 31 this work is limited to a small area in the open parking lot.…”
Section: Related Workmentioning
confidence: 99%
“…Searching for empty parking spaces leads to cruising and frequent stops which increases CO 2 emissions. Paidi et al [ 22 ] found that excess CO 2 emissions and non-optimal were mainly observed during visitor peak hours when there were limited or no empty parking spaces in the region of interest, which also leads to excess cruising. A facility location and allocation scheme was engaged to determine the optimal number and locations of public parking lots in Aydin’s study.…”
Section: Literature Reviewmentioning
confidence: 99%